Prevalence and factors associated with overweight and obesity among healthcare workers in Pejabat Kesihatan Daerah Melaka Tengah - Syafiq Taib; Siti Nor Mat; Norzaher Ismail; Fairuz Rahmat; Noor Aizam Said; Shamsul Azhar Shah (Penerbit Universiti Kebangsaan Malaysia, 2019)
Introduction Overweight and obesity are a serious public health problem globally. Healthcare workers in some countries have been reported to be having a high prevalence of being overweight despite them being well informed of the aetiology and risks of excessive body weight. However, the problem of being overweight and obese among Malaysian healthcare workers is still poorly understood. The aim of this study is to assess the prevalence and factors associated with overweight and obesity among healthcare workers in Pejabat Kesihatan Daerah (PKD) Melaka Tengah. Methods This is a cross sectional study conducted between June till August 2018 involving 702 respondents sampled from all health facilities under PKD Melaka Tengah. Demographic, socio-economic and lifestyle data was collected using questionnaires whilst anthropometric measurements were taken using the electronic weighing scale and height measuring bar. Results Mean age was 35.81 years and overall prevalence of overweight/obesity was 55.6%. Prevalence of overweight, class I obesity, class II obesity and class III obesity was 34.3%, 14.2 %, 4.8% and 2.1% respectively. The identified risks of being overweight were those aged forty and above (OR: 2.00, 95%CI: 1.39-2.85), non-Chinese (OR: 4.97, 95%CI: 2.13-11.62), married (OR: 1.77, 95%CI: 1.15-2.73), big family size (OR: 1.43, 95%CI: 1.07-1.99), underlying NCD (OR: 1.73, 95%CI: 1.24-2.42), family history of NCD (OR: 1.94, 95%CI: 1.33-2.82), and sedentary lifestyle (OR: 1.52, 95%CI: 1.07-2.17). Conclusions We found a higher prevalence of overweight/obesity among healthcare workers in PKD Melaka Tengah compared to the general population. Older age group and non-Chinese ethnicity emerged as the most conspicuous factors of overweight/obesity.